Unbalanced Neonatal CD4+ T-Cell Immunity - Debock, Isabelle; Flamand, Véronique (Frontiers in Immunology, 2014)
In comparison to adults, newborns display a heightened susceptibility to pathogens and a propensity to develop allergic diseases. Particular properties of the neonatal immune system can account for this sensitivity. Indeed, a defect in developing protective Th1-type responses and a skewing towards Th2 immunity characterize today the neonatal T-cell immunity. Recently, new findings concerning Th17, regulatory helper T-cell and follicular helper T-cell subsets in newborns have emerged. In some circumstances, development of effector inflammatory Th17-type responses can be induced in neonates, while differentiation in regulatory T cells appears to be a default program of neonatal CD4+ T cells. Poor antibody production, affinity maturation and germinal center reaction in vaccinated neonates are correlated with a limiting expansion of TFH lymphocytes. We review herein the factors accounting for and the implications of the unbalanced neonatal helper T-cell immunity.